Využití prostředků umělé inteligence na finančních trzích - Turoň, Michal (Vysoké učení technické v Brně. Fakulta podnikatelská, 2013)
Diplomová práca sa zaoberá problematikou obchodovania na komoditných trhoch, konkrétne zlata. Využíva pritom prostriedky umelej inteligencie, presnejšie nelineárne autoregresné neurónové siete. Účelom je predikcia cien zlata pomocou indikátorov, ktoré majú na zlato vplyv.

This master thesis deals with issue of trade on commodity market, especially the gold. It uses the artificial intelligence resources, more accurate non-linear auregressive neural network. The purpose is the prediction of the gold prices by indicators which has impact on the gold.
The Use of Means of Artificial Intelligence for the Decision Making Support on Financial Markets
Keywords: Umelá inteligencia; neurónové siete; predikcia; kapitálové trhy; komodita; zlato; technická analýza; simulácia; Artificial intelligence; neural network; prediction; stock market; commodity; gold; technical analysis; simulation